In vivo deep network tracing reveals phosphofructokinase-mediated coordination of biosynthetic pathway activity in the myocardium. (January 2022) - Fulghum, Kyle L.; Audam, Timothy N.; Lorkiewicz, Pawel K.; Zheng, Yuting; Merchant, Michael; Cummins, Timothy D.; Dean, William L.; Cassel, Teresa A.; Fan, Teresa W.M.; Hill, Bradford G.
Abstract: Glucose metabolism comprises numerous amphibolic metabolites that provide precursors for not only the synthesis of cellular building blocks but also for ATP production. In this study, we tested how phosphofructokinase-1 (PFK1) activity controls the fate of glucose-derived carbon in murine hearts in vivo . PFK1 activity was regulated by cardiac-specific overexpression of kinase- or phosphatase-deficient 6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase transgenes in mice (termed Glyco Lo or Glyco Hi mice, respectively). Dietary delivery of 13 C6 -glucose to these mice, followed by deep network metabolic tracing, revealed that low rates of PFK1 activity promote selective routing of glucose-derived carbon to the purine synthesis pathway to form 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR). Consistent with a mechanism of physical channeling, we found multimeric protein complexes that contained phosphoribosylaminoimidazole carboxylase (PAICS)—an enzyme important for AICAR biosynthesis, as well as chaperone proteins such as Hsp90 and other metabolic enzymes. We also observed that PFK1 influenced glucose-derived carbon deposition in glycogen, but did not affect hexosamine biosynthetic pathway activity. These studies demonstrate the utility of deep network tracing to identify metabolic channeling and changes in biosynthetic pathway activity in the heart in vivo and present new potential mechanisms by which metabolic branchpoint reactions modulate biosynthetic pathways. Graphical abstract: Unlabelled Image Highlights: Deep network tracing is a useful tool for assessing in vivo changes in cardiac biosynthetic pathways. Cardiac phosphofructokinase regulates ancillary biosynthetic pathway activity. Low cardiac phosphofructokinase activity selectively directs glucose-derived carbon toward AICAR biosynthesis.